Initial management strategies for dyspepsia. - Delaney, B; Innes, M; Deeks, J; Wilson, S; Oakes, R; Moayyedi, P; Hobbs, F; Forman, D (2000)
BACKGROUND: This review considers management strategies (combinations of initial investigation and empirical treatments) for dyspeptic patients. OBJECTIVES: To determine the effectiveness, acceptability, and cost effectiveness of the following initial management strategies for patients presenting with dyspepsia (a) initial pharmacological therapy (including endoscopy for treatment failures) (b) early endoscopy (c) testing for Helicobacter pylori and endoscope only those positive (d) H.pylori eradication therapy with or without prior testing. SEARCH STRATEGY: Trials were located through electronic searches and extensive contact with trialists. SELECTION CRITERIA: All randomised controlled trials of dyspeptic patients presenting in primary care. DATA COLLECTION AND ANALYSIS: Data was collected on dyspeptic symptoms, quality of life and use of resources. MAIN RESULTS: Ten papers reporting 12 comparisons were found. Trials comparing proton pump inhibitors (PPI) with antacids (2 trials) and H2 receptor antagonists (3 trials), and of early endoscopy compared with initial acid suppression (3 trials) were pooled. PPIs were significantly more effective than both H2RA s and antacids. Relative risks (RR) and 95% CI were, for PPI: antacid 0.72 (0.64-0.80), PPI: H2RA 0.63 (0.47-0.85). Results for other drug comparisons were either absent or inconclusive. Early endoscopy was not more effective than initial prescribing (RR 0.90 (0.77-1.04), but current studies lack power. No eligible trials of H.pylori test and endoscopy or test and eradicate were found. REVIEWER'S CONCLUSIONS: PPIs are effective in the treatment of dyspepsia in these trials which may not adequately exclude patients with gastro-oesophageal reflux disease. The relative efficacy of H2RA and PPI is uncertain. Early investigation may benefit some patients with dyspepsia. The review will be updated shortly with several large trials that have recently been completed.